Non-Foster Matching Circuit Design via Tunable Inductor for VLF Receive Loop Antennas - Yalong Yan; Chao Liu; Huaning Wu; Yinghui Dong (International Journal of Antennas and Propagation)
This paper presents a non-Foster matching circuit (NFC) for very low frequency (VLF) receive loop antennas. A 1 ⁎ 1 m VLF receive loop antenna was designed with a CMOS switch-based tunable inductor built into the NFC. The NFC can be applied to different VLF loop antennas by adjusting the number and inductance of the cells in the tunable inductor. A loop antenna was matched to the designed NFC with −10 dB S11 fractional bandwidth, marking a 383% improvement as well as enhanced transducer gain (S21) compared to most bands in passive matching (over 15–30 kHz). The noise and received signal-to-noise ratio (SNR) of the matching network were assessed to find that, with a low noise floor level (4 dB) receiver, the SNR of the passive loaded antenna performs better than the non-Foster loaded antenna in VLF.